The Authority of Teacher in Madrasah Based of Islamic Boarding School - Rohmad, Muhammad Ali (EDUKASIA, 2020)
Teachers are obliged to possess authority to increase pedagogical interaction effectivity. However, there has been a shift in the meaning of authority so that an in-depth study is carried out on the dimensions of teacher authority, factors that influence the teacher authority, and the dynamics of teacher authority in Madrasah based of Islamic boarding school (pesantren). This research is a qualitative research by using interview, observation and documentation methods to collect the data. The data analysis includes data reduction, data display, and conclusion drawing/verification. The results show: 1) Authority is defined as strength to be admired accompanied by respect so as to bring obedience. The dimensions of teacher authority include spiritual, cognitive, affective, skills, social and physical: 2) There are at least 3 (three) factors that can increase the teacher authority, namely assertiveness, responsibility and patience; 3) The teachers authority from inside the pesantren (ndalem) is in the form of traditional authority, while teachers from outside the pesantren must strive to gain authority in the form of charismatic authority or even legal rational authority.